2012
DOI: 10.1016/j.rinim.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

IgM phosphorylcholine antibodies inhibit cell death and constitute a strong protection marker for atherosclerosis development, particularly in combination with other auto-antibodies against modified LDL

Abstract: Group I anti-PC antibodies, particularly of the IgM class, are independent protection markers for atherosclerosis progression. One potential mechanism of action is inhibition of LPC-induced cell cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 34 publications
8
54
1
Order By: Relevance
“…Moreover, cross-sectional studies have shown that higher concentrations of circulating IgM anti-PC in lupus are associated with a lower probability of a cardiovascular event, such as a myocardial infarction or stroke [84, 89] and lower prevalence of atherosclerotic plaques in the carotids [94]. In non-autoimmune patients, prospective screening has demonstrated that levels IgM anti-PC may provide a biomarker for prediction of preclinical cardiovascular disease associated with atherosclerotic plaque burden as measured by ultrasound intima-media thickness [95, 96]. Retrospective studies have also suggested that lower baseline levels of IgM anti-PC may be predictive for stroke [97, 98], myocardial infarction [99] or overall atherosclerotic cardiovascular disease incidence [100].…”
Section: Protective Natural Igm In Clinical Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cross-sectional studies have shown that higher concentrations of circulating IgM anti-PC in lupus are associated with a lower probability of a cardiovascular event, such as a myocardial infarction or stroke [84, 89] and lower prevalence of atherosclerotic plaques in the carotids [94]. In non-autoimmune patients, prospective screening has demonstrated that levels IgM anti-PC may provide a biomarker for prediction of preclinical cardiovascular disease associated with atherosclerotic plaque burden as measured by ultrasound intima-media thickness [95, 96]. Retrospective studies have also suggested that lower baseline levels of IgM anti-PC may be predictive for stroke [97, 98], myocardial infarction [99] or overall atherosclerotic cardiovascular disease incidence [100].…”
Section: Protective Natural Igm In Clinical Surveysmentioning
confidence: 99%
“…However, a recent report found that the anti-carbohydrate antibodies in pooled IgG in intravenous immunoglobulin (IVIG) preparations are not restricted to IgG2 but can be associated with other subclasses as well [110]. IgG of different subclasses may convey functional differences, and it may therefore be relevant that a recent clinical survey found correlative evidence that IgG1 anti-PC levels are more strongly associated with protective properties in atherosclerosis than IgG2 [95]. This topic remains controversial, in part because they will require characterization of the fine specificity and functional properties of monoclonal anti-PC antibodies in the context of different subclasses.…”
Section: Natural Igg Antibodiesmentioning
confidence: 99%
“…Human anti-PC could be anti-atherogenic and decrease risk of CVD by anti-inflammatory effects (107), inhibition of oxLDL-uptake through scavenger receptors (111) and inhibition of LPC-induced cell (112). In mouse models, the anti-inflammatory effect of anti-PC was confirmed, and facilitating phagocytosis was reported as one mechanism.…”
Section: Diabetes and Causes Of Immune Activation In Atherosclerosismentioning
confidence: 99%
“…This is supported by clinical studies, animal and in vitro experiments (50). As discussed, mechanisms include anti-inflammatory (107, 167), inhibition of cell death (112), and decreased uptake of oxLDL in macrophages (105). Further, administration of immunoglobulins has shown promising results in animal studies (168).…”
Section: Treatment Against Inflammation and Immune Activation To Amelmentioning
confidence: 99%
“…Mechanisms by which human anti-PC could ameliorate atherosclerosis and CVD include: anti-inflammatory effects, inhibition of pro-inflammatory effects by inflammatory phospholipids [42], inhibition of uptake of oxLDL through scavenger receptors [43] and inhibition of cell death induced by LPC, a major inflammatory phospholipid [44]. In another paper, the inflammatory effect of anti-PC is also confirmed in a mouse model, in which facilitating phagocytosis is described as one mechanism.…”
Section: Introductionmentioning
confidence: 99%